OCCURRENCE AND SOURCES OF PRIORITY POLYCYCLIC AROMATIC HYDROCARBONS IN SEDIMENT SAMPLES ALONG THE AURÁ RIVER (NORTHERN BRAZIL) - Santos, Camila Carneiro; Soares, Lorena da Silva; Corrêa, José Augusto Martins (Geochimica Brasiliensis, 2016)
Polycyclic aromatic hydrocarbons (PAHs) are organic compounds generated by the organic matter incomplete combustion and there are sixteen PAHs (16-USEPA-PAHs) considered as priority in environmental studies by the Environmental Protection Agency of the United States. The aims of this work was to determine the major source and spatial variations of the 16-USEPA-PAHs in the sediments of Aurá river. North of the Aurá river exists a landfill site, currently disabled, which operated in an uncontrolled and irregular manner for about 24 years. PAHs were identified and quantified in sediment from 10 sites inside the river and in its mouth. The samples were analyzed by HPLC/UV-Vis-DAD to assess the degree of contamination. Total PAH concentrations (ΣPAHs) ranged from 3 824.21 to 15 693.91 ng g-1. In general, a concentration gradient was observed. The sediment samples were classified as highly contaminated (ΣPAHs > 500 ng g-1). Compared to other areas, PAH concentrations in Aurá river are relatively similar to highly industrialized and polluted places. The ratios of low molecular weight/high molecular weight PAHs (LMW/HMW), indicates a pyrolytic origin, which have shown to be mostly from waste combustion.